(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The article focuses on the analysis and optimization of the technological process at the Ferry Complex for freight transportation, connecting maritime and railway transport. A key feature of this complex is the presence of railway networks with different track gauges, which necessitates specialized operations such as bogie exchange and additional shunting activities, leading to specific challenges in managing technological operations. To optimize technological operations or the required infrastructure at the terminal yards, mathematical modeling and simulations are considered. These simulations include optimization algorithms for resource allocation, heuristic and metaheuristic approaches for the distribution of freight flows, and bogie exchange. The simulations allow for the assessment of the impact of changes in technological processes and support decision-making to improve the complex’s performance, as well as its infrastructure, depending on the volume of freight flows, including hazardous materials cargo. The Ferry Terminal is modeled as a complex system, composed of various interacting technological subsystems, which are formalized as queueing systems. This approach allows for the use of well-known analytical formulas from Queueing Theory to represent the technological process. Formulas are derived to determine the duration of technological operations depending on the type of cargo (hazardous or not), the dwell time of the wagons in the complex, and the number of requests per subsystem. This enables the optimization of the technical equipment at the terminal, based on the size of the processed wagon flow. The model is developed for the Varna Ferry Complex, which handles a large volume of freight and involves specific logistics processes related to the handling of freight wagons. The complex includes a bogie exchange facility where wagons undergo the process of replacing running gear to meet the requirements of different track gauges. The technological operations are formalized, evaluated, and various subsystem parameters are determined. As a result, depending on the size of the wagon flow, the technological process or technical equipment of the complex can be optimized. Modernization and optimization of the complex will lead to improved capacity and competitiveness, providing greater flexibility and efficiency in freight handling.